Are International R&D Spillovers Costly for the United States? - Luintel, Kul B.; Khan, Mosahid (The Review of Economics and Statistics, 2004)
Coe and Helpman, among others, report positive and equivalent R&D spillovers across groups of countries. However, the nature of their econometric tests does not address the heterogeneity of knowledge diffusion across countries. We empirically examine these issues in a sample of 10 OECD countries by extending both the time span and the coverage of R&D activities in the data set. We find that the elasticity of total factor productivity with respect to domestic and foreign R&D stocks is extremely heterogeneous across countries and that data cannot be pooled. Thus, panel estimates conceal important cross-country differences. The United States appears to be a net loser in international R&D spillovers. Our interpretation is that when competitors catch up technologically, they challenge U.S. market shares and investments worldwide.